Elevated shear stress modulates heterogenous cellular subpopulations to induce vascular remodeling - Fischer, Katharina; Henn, Dominic; Zhao, Eric T.; Sivaraj, Dharshan; Litmanovich, Ben; Hahn, William W.; Hostler, Andrew C.; Mojadidi, Sultana M.; Gonzalez, Javier; Knochel, Amelia B.; Mora Pinos, Maria Gracia; Holley, Jared; et al. (Tissue engineering, 2024)
Rationale: Elevated shear stress (ESS) induces vascular remodeling in veins exposed to arterial blood flow, which can lead to arteriovenous (AV) fistula failure. The molecular mechanisms driving remodeling have not been comprehensively examined with a single-cell resolution before. - Objective: Using an in vivo animal mode, single-cell RNA sequencing, and histopathology, we precisely manipulate blood flow to comprehensively characterize all cell subpopulations important during vascular remodeling. - Methods: AV loops were created in saphenous vessels of rats using a contralateral saphenous vein interposition graft to promote ESS. Saphenous veins with no elevated shear stress (NSS) were anastomosed as controls. - Findings: ESS promoted transcriptional homogeneity, and NSS promoted considerable heterogeneity. Specifically, ESS endothelial cells (ECs) showed a more homogeneous transcriptional response promoting angiogenesis and upregulating endothelial-to-mesenchymal transition inhibiting genes (Klf2). NSS ECs upregulated antiproliferation genes such as Cav1, Cst3, and Btg1. In macrophages, ESS promoted a large homogeneous subpopulation, creating a mechanically activated, proinflammatory and thus proangiogenic myeloid phenotype, whereas NSS myeloid cells expressed the anti-inflammatory and antiangiogenetic marker Mrc1. - Conclusion: ESS activates unified gene expression profiles to induce adaption of the vessel wall to hemodynamic alterations. Targeted depletion of the identified cellular subpopulations may lead to novel therapies to prevent excessive venous remodeling, intimal hyperplasia, and AV fistula failure.
Gesehen am 27.11.2024